An investigation on microstructural, physical, and radiation shielding properties Yb2O3 oxide dispersion-strengthened 316L-SS alloys - Almisned, Ghada; Yayla, Nihal; Albayrak, Muhammet Gokhan; Guler, Omer; Sen Baykal, Duygu; Alkarrani, Hessa; Tekin, H. O. (Springer Heidelberg, 2025)
Oxide dispersion-strengthened alloys have emerged as a highly effective solution to address the physical, structural, and shielding challenges faced by traditional alloys in nuclear environments. This study presents a comprehensive evaluation of the microstructural, mechanical, and radiation shielding properties of Yb2O3 oxide dispersion-strengthened 316L stainless steel composites at varying Yb2O3 concentrations such as 1%, 5%, 10%, and 20% by weight. XRD analysis revealed lattice distortions, with crystallite sizes decreasing from 11.2267 nm to 9.3351 nm. SEM/EDX analyses confirmed homogeneous Yb2O3 dispersion at lower concentrations, with agglomeration at 20% Yb2O3. The mass attenuation coefficient increased from 56.103 cm2/g to 65.919 cm2/g at 0.015 MeV, marking a 17.5% enhancement. HVL decreased by 40.68% at 0.2 MeV for the 20% Yb2O3 sample. Additionally, the 20% Yb2O3 composite showed nearly 33% lower transmission factor at 3.0 cm thickness and 0.662 MeV. It can be concluded that Yb2O3 reinforcement significantly enhances the microstructural, and gamma-ray attenuation properties of 316L-SS composites, positioning them as promising materials for advanced nuclear shielding and structural applications.
Keywords: 316L stainless-steel; Rare-earth oxide; Europium oxide; Nuclear radiation shielding